Risk of Infection After Allograft Anterior Cruciate Ligament Reconstruction: Are Nonprocessed Allografts More Likely to Get Infected? A Cohort Study of Over 10, 000 Allografts. Issue 4 (March 2018) - Yu, Anthony; Prentice, Heather A.; Burfeind, William E.; Funahashi, Tadashi; Maletis, Gregory B.
Background: Allograft tissue is frequently used in anterior cruciate ligament reconstruction (ACLR). It is often irradiated and/or chemically processed to decrease the risk of disease transmission, but some tissue is aseptically harvested without further processing. Irradiated and chemically processed allograft tissue appears to have a higher risk of revision, but whether this processing decreases the risk of infection is not clear. Purpose: To determine the incidence of deep surgical site infection after ACLR with allograft in a large community-based sample and to evaluate the association of allograft processing and the risk of deep infection. Study Design: Cohort study; Level of evidence, 3. Methods: The authors conducted a cohort study using the Kaiser Permanente Anterior Cruciate Ligament Reconstruction Registry. Primary isolated unilateral ACLR with allograft were identified from February 1, 2005 to September 30, 2015. Ninety-day postoperative deep infections were identified via an electronic screening algorithm and then validated through chart review. Logistic regression was used to evaluate the likelihood of 90-day postoperative deep infection per allograft processing method: processed (graft treated chemically and/or irradiated) or nonprocessed (graft not irradiated or chemically processed). Results: Of 10, 190 allograft cases, 8425 (82.7%) received a processed allograft, and 1765 (17.3%) received a nonprocessed allograft. There were 15 (0.15%) deep infections during the study period: 4 (26.7%) coagulase-negative Staphylococcus, 4 (26.7%) methicillin-sensitive Staphylococcus aureus, 1 (6.7%) Peptostreptococcus micros, and 6 (40.0%) with no growth. There was no difference in the likelihood for 90-day deep infection for processed versus nonprocessed allografts (odds ratio = 1.36, 95% CI = 0.31-6.04). Conclusion: The overall incidence of deep infection after ACLR with allograft tissue was very low (0.15%), suggesting that the methods currently employed by tissue banks to minimize the risk of infection are effective. In this cohort, no difference in the likelihood of infection between processed and nonprocessed allografts could be identified.